Eksistensi dan Urgensi Peraturan Menteri dalam Penyelenggaraan Pemerintahan Sistem Presidensial - Ridwan Ridwan (Jurnal Konstitusi, 2022)
This research aims to analyze Ministerial Regulations in Indonesian governmental affairs. It is normative legal research with the statute and conceptual approaches. The results of this research show in a presidential system, the position of ministry is a president’s assistant. Thus, they could not be granted attributed authorities through an act. However, the ministerial regulations remain necessary in governmental affairs, especially as a technical law for governmental and presidential regulations. They regulate and operate certain sectors of each ministry. In addition, specific governmental sectors could not be regulated proportionally by using either presidential or even governmental regulations because a governmental regulation has specific legal aims as technical provisions of acts.